536. Clostridium difficile Colonization in the First Year of Life. (26th November 2018) - Clayton, Jason A; Cadnum, Jennifer; Senders, Shelly; Donskey, Curtis J; Toltzis, Philip
Abstract: Background: Recent years have witnessed an explosive increase in community-associated Clostridium difficile infection (CA-CDI) in adults. Contact with infants, a population known to be asymptomatically colonized by C. difficile (CD), has been identified as a risk factor for CA-CDI, rendering it vital to explore the epidemiology and determinants of acquisition in babies. Methods: In this prospective cohort study, healthy infants attending a demographically diverse suburban pediatric practice were enrolled at birth and followed through their 2-month, 6-month, and 12-month well child visit. At each visit, stool samples were collected, and questionnaires including interim exposure to potential risk factors for CD acquisition were administered. Stool was inoculated on pre-reduced CCFA agar with a graduated loop. Among CD isolates, toxin genes were identified by PCR. Results: Fifty infants were recruited; 90% of samples and questionnaires were completed. The average gestational age was 39 weeks and 46% were male. Twenty-eight (56%) infants had at least one sample positive for CD during the study: cross sectional incidence was 0/50 at birth; 9/47 (19%) at 2 months; 22/43 (51%) at 6 months; 6/37 (16%) at 1 year. Of those with positive stool cultures, three(11%) tested positive at multiple visits. Of the 37 (81%) isolates, 30 were PCR-positive for CD toxin. Five stool samples harbored >4.5 log10 cfu of toxigenic CD/g of stool. Proportions of CD+ vs. CD− subjects, respectively, with interim exposure to selected CD risk factors at each visit were as follows: infant healthcare visit 45% vs. 42%; household member healthcare visit 17% vs. 23%; household member with diarrhea 14% vs. 29%; antibiotic exposure 5% vs. 4%; antacid exposure 7% vs. 3%, all P > 0.05. Regarding risks for acquisition of enteric pathogens in general: breastmilk-including nutrition 57% vs. 73% ( P < 0.05 only at 2-month visit); 48% CD+ infants had interim daycare attendance vs. 25% CD− (but P > 0.05 at each visit). Conclusion: Asymptomatic carriage of toxigenic CD occurred in over half of healthy infants during the first year of life, and several had a high organism burden that could increase the risk for transmission. While daycare attendance was more common among colonized infants, the majority of infants who were CD+ had no daycare exposure. Disclosures: All authors: No reported disclosures.